2022
DOI: 10.21608/ejap.2022.131455.1039
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Activity, Semen Characteristics and Testosterone Levels in Mature Male Rabbits Treated With Hormonal and Non-Hormonal Preparations

Abstract: This study was carried out to determine the influence of human chorionic gonadotropin (hCG), L-Carnitine (LC) and Royal jelly (RJ) treatments on Sexual activity, semen characteristics and testosterone levels of mature New Zealand White (NZW) males rabbit. A total of 20 NZW bucks were randomly assigned into four groups (5 bucks/each).The1 st group bucks were left without treatment (Control group). The Rabbit bucks of the 2 nd group injected IM with 50 IU of hCG / male / weekly for 6 weeks (hormonal group). Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…These findings are based on the findings of ginger's effects on animals. [184] [185] The sperm count, motility, and viability of diabetic rats with infertility were dramatically enhanced when the rats were fed a mixture of ginger and cinnamon, according to the findings of research conducted in Greece. In another study, Abo-Ghanema and colleagues found that treating infertile rats with ginger and L-carnitine was successful in restoring their fertility.…”
Section: Gingermentioning
confidence: 94%
“…These findings are based on the findings of ginger's effects on animals. [184] [185] The sperm count, motility, and viability of diabetic rats with infertility were dramatically enhanced when the rats were fed a mixture of ginger and cinnamon, according to the findings of research conducted in Greece. In another study, Abo-Ghanema and colleagues found that treating infertile rats with ginger and L-carnitine was successful in restoring their fertility.…”
Section: Gingermentioning
confidence: 94%
“…Propolis acts as an antioxidant agent, owing to its phenolic compounds especially flavonoids which acts as free radical scavengers and protect the tissues from their toxicological effects. Also, (Coskun et al, 2005;Ali et al, 2022) proved that propolis and its components has a protective role against the toxic effects of diabetes in rats, as the levels of liver enzymes ALT and AST and lipid peroxidation products (lipid peroxidation) represented by elevated TBARS decreased significantly in serum in the group treated with propolis. As well as a significant increase in the level of antioxidants enzymes such as (superoxide dismutase, catalase, glutathione peroxidase and Glutathione S-transferase) in the liver, kidney and heart compared with the diabetic group.…”
Section: Kidney Tissuesmentioning
confidence: 97%
“…Most food sources are safe. Avocados, nuts, seeds, green leafy vegetables, fortified cereals, vegetables, grape seeds, and canola oil are natural vitamin E sources [26].…”
Section: Vitaminmentioning
confidence: 99%
“…They contain vitamin E, which is beneficial to the nails and skin. Avocados are high in vitamin B6, potassium, and monounsaturated fats [26,37]. These promote healthy circulation and a strong heart, both of which are required for sex.…”
Section: Avocado (Asparagus Officinalis)mentioning
confidence: 99%